Growth phase-dependent RpoS levels in Escherichia coli laboratory and environmental strains - Haghighi, Pardis (My University, 2016)
RNA polymerase and the sigma factors in Escherichia coli play role in maintaining the bacterial transcriptional profile in dynamic environmental conditions during growth cycle. Previously, transcriptom analysis between E. coli laboratory strain MG1655 and pathogenic strain EDL933 showed that a lot of genes are highly RpoS-dependent in EDL933 without RpoD to compete against RpoS. In the first project, the RpoD level was examined in these two strains. The same RpoD level between the two E. coli strains was shown suggesting the independent expression of RpoS regulon. In prototypical E. coli K12 MG1655 laboratory strain, RpoS levels, the stress-response sigma factor, are not detectable during exponential phase while several genes are controlled by RpoS in this phase. Although, RpoS levels in E. coli pathogenic strain O157:H7 was higher during exponential phase, the RpoS expression pattern in other isolates of E. coli was not known. In second project, the E. coli environmental isolates were examined as we have access to a large number of isolates, collected from a variety of gut to aquatic sources. To examine if RpoS in environmental isolates has exponential phase expression similar to that of laboratory strains, immunoblots were performed on forty isolates at exponential phase (OD600 ~ 0.3). Twelve isolates showed higher levels of RpoS protein compared to laboratory strain during exponential phase. Also, the immunoblot analysis on some of the isolates at early stationary phase (OD600 ~ 1.5) and 24 h after subculture demonstrate the decrease in expression of RpoS protein at stationary phase to overnight culture. This finding was different from the RpoS expression in E. coli K12 laboratory strain. In conclusion, the relatively lower levels of RpoS in the laboratory strains might occur due to selection for attenuation in RpoS levels in the laboratory strains after being cultivated for many years in laboratory conditions.